Biomass analysis and carbon reserve on some cocoa planting systems in Bantaeng district. Issue 1 (March 2020) - Asrul, L; Mustari, K; Kaimuddin,; Faradilla, L
Abstract: Cocoa plantations have ecological functions as carbon sinks and depositors. Cocoa absorbs CO2 during photosynthesis, then converts it to carbohydrates by storing it in the form of biomass in roots, trees, and leaves. The purpose of this study was to determine the carbon uptake of cocoa trees and tree growers, undergrowth, necromasses, carbon uptake at the root and carbon uptake in soils in several cocoa planting systems implemented in Bantaeng Regency, South Sulawesi. Sampling is done by a purposive sampling method with the basic consideration of the type, density and cropping system applied. Biomass estimation is used the non-destructive method by measuring the diameter at breast height (DBH, 1.3 m) and height of cacao and shade plants. Carbon storage in cocoa plants is distinguished by several cropping systems, namely K1 (monoculture harvesters) and K2 (multistrata harvesters). The results showed that carbon reserves in Bantaeng Regency were 32.38 tons/Ha.